ANALISA KINERJA KEUANGAN PADA PT. BANK RAKYAT INDONESIA (BRI) UNIT SIMPANG RIMBO - Luluq il Jannah; Abdilla Rungki P; Ariny Asyhari; Ratih Kusumastuti (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
Performance appraisal aims to determine progress and to increase the trust of external parties. There are two types of assessment of company performance, namely the assessment of financial performance and non-financial performance. Financial performance is an analysis carried out to see how far a company has carried out by using the rules of financial implementation properly and correctly. The research methodology used is based on data and data sources, data collection methods, operational definitions, and analytical methods. The analytical method used is financial ratio analysis which is a form of quantitative analysis. In 2020, the current ratio, quick ratio and cash ratio are respectively 115%, 66% and 52% and in 2021 they are 113%, 64% and 53%. The cash turnover ratios in 2020 and 2021 are 2 times and 4 times. Debt to Asset Ratio in 2020 and 2021 is 46% and 41%. Working capital turnover for 2020 and 2021 is 2 times and 4 times. Fixed asset turnover for 2020 and 2021 is 0.23 times, and 0.28 times. Meanwhile, total asset turnover for 2020 and 2021 is 0.12 times and 0.16 times. The net profit margin in 2020 and 2021 is 37% and 35%. After conducting research on the performance of the BRI Simpang Rimbo Besar Unit, it can be concluded that the performance of the BRI Simpang Rimbo Besar Unit for the periods of 2020 and 2021 from a liquidity standpoint is quite good as well as from a solvency perspective. is good enough. However, in terms of activity and profitability, the performance of BRI Simpang Rimbo Unit is not good. For this reason, the authors suggest that the BRI Simpang Rimbo Besar Unit further improve promotions and service levels to attract potential customers